From Campus To CEO: Unveiling The Entrepreneurial Intentions Among University Students: Investigating The Mediating Effect Of Role Model And Moderating Role Of University Support - Muhammad Adeel Abid , Muhammad Mohsin , Muhammad Tofique , Nimra Azeem , Sana Shahzadi , Somia (Migration Letters, 2024)
This study aims to examine the factors influencing the formation of entrepreneurial intention among university students. Specifically, this research explores the impact of entrepreneurial education and passion for entrepreneurship in terms of invention and founding, recognition of opportunities, and attitude toward entrepreneurship. This study also investigates the potential mediating influence of role model and the moderating impact of perceived university support. The data using non-probabilistic purposive sampling were collected via a Google survey from 250 university students who studied entrepreneurship subjects in their degree programs. The result, analyzed using Smart PLS4, shows that every independent variable strongly influences the entrepreneurial intention and that the role model and university support help promote this intention more effectively. Policymakers, academians, and government institutions could use the actual data to develop ways to encourage university students to start their own businesses.